Supersizing and upselling in fast food restaurants and bars: what responsibility have companies got if customers choose to consume too much fast food or too much alcohol? - Pratten, John (Henry Stewart Talks, 2011)
Problems created by the misuse of alcohol and fast food, Retailers and ethics, The concept of Corporate Social Responsibility, CSR expectations from the providers of ethically dubious or socially undesirable products, The ethical answer, The legal approach, The role of the owners/managers, The economic approach, Who can be blamed for these problems?, The managerial approach, The role of government, The role of society, Conclusions